Influence of Spatial Scale on Structure of Soil Bacterial Communities across an Arctic Landscape - Malard, Lucie A. (Appl Environ Microbiol, 2021)
Bacterial community composition is largely influenced by environmental factors, and this applies to the Arctic region. However, little is known about the role of spatial factors in structuring such communities. In this study, we evaluated the influence of spatial scale on bacterial community structure across an Arctic landscape. Our results showed that spatial factors accounted for approximately 10% of the variation at the landscape scale, equivalent to observations across the whole Arctic region, suggesting that while the role and magnitude of other processes involved in community structure may vary, the role of dispersal may be stable globally in the region. We assessed dispersal limitation by identifying the spatial autocorrelation distance which would be required in order to obtain fully independent samples as approximately 60 m, and this may inform future sampling strategies in the region. Finally, indicator taxa with strong statistical correlations with environmental variables were identified. However, we showed that these strong taxon-environment associations may not always be reflected in the geographical distribution of these taxa. IMPORTANCE The significance of this study is 3-fold. It investigated the influence of spatial scale on the soil bacterial community composition across a typical Arctic landscape and demonstrated that conclusions reached when examining the influence of specific environmental variables on bacterial community composition are dependent upon the spatial scales over which they are investigated. This study identified a dispersal limitation (spatial autocorrelation) distance of approximately 60 m, required to obtain samples with fully independent bacterial communities and, therefore, should serve to inform future sampling strategies in the region and potentially elsewhere. The work also showed that strong taxon-environment statistical associations may not be reflected in the observed landscape distribution of the indicator taxa.